Evidence for hydrogen-sulfide as a novel modulator of Hyperpolarization-activated Cyclic Nucleotide-gated (HCN) channels in human atrial cardiomyocytes. (10th June 2022) - Balducci, V; Gencarelli, M; Laurino, A; Spinelli, V; Stefano, P; Cerbai, E; Sartiani, L
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): M.I.U.R. PRIN 2017 Evidence for hydrogen-sulfide as a novel modulator of Hyperpolarization-activated Cyclic Nucleotide-gated (HCN) channels in human atrial cardiomyocytes Background: Hydrogen sulfide (H2S) is an endogenous gasotransmitter that controls several physiological and pathological processes in mammalian organs. H2S is synthesized by endogenous enzymes and directly regulates the function of target proteins by sulfhydration of cysteine residues and/or indirect effects mediated by modification of intracellular cyclic nucleotide (cAMP/cGMP) levels. In the cardiovascular system, H2S activates protective responses aimed to counterbalance pathological processes, such as those involved in glucose dysmetabolism, vasal constriction, oxidative stress and cytotoxicity. In cardiac cells, H2S regulates electrogenesis through the modulation of different ion channels, comprising potassium, calcium and TRP channels. No information is available on the effects of H2S on the funny current (If), which is involved in cardiac pacemaking and working myocyte electrogenesis. Purpose: The aim of this study was to assess whether H2S modulates the properties of If in human atrial myocytes. If is mediated by Hyperpolarization-activated Cyclic Nucleotide-gated (HCN) channels, which are expressed in human atria and are directly regulated by intracellular cAMP/cGMP levels. Methods: Human atrial cardiomyocytes were isolated by enzymatic and mechanical digestion from atrial specimens of patients undergoing cardiac surgery. The acute effects of H2S on If were tested by single-cell patch-clamp recordings using increasing concentrations of NaHS as H2S donor. Results: High NaHS concentrations increased If conductance at all potential tested. At physiological potential (-80 mV), relative If conductance changed from 0.33±0.08 to 0.45±0.11 and 0.60±0.11 at 10 and 100 µM concentrations, respectively (p<0.05, n=5-7), while half-maximal activation potential (V½) was shifted from -92.4±0.9 to -83.9±0.7 and -82.4±0.4 mV, respectively (p<0.05, n=5-7). Conversely, low NaHS concentrations reduced If conductance that at -80 mV changed to 0.23±0.07 and 0.25±0.06 at 1 and 5 µM concentrations, respectively (p<0.05, n=5-7). Accordingly, at low NaHS concentration If V½ showed a trend toward less positive potentials. Both high and low concentrations did not modify If kinetics. Conclusions: H2S exerts a dual, concentration-dependent effect on If expressed in human atrial cardiomyocytes. This response is similar to that induced by NO, a different gas signaling molecule. The effect of H2S on If properties may be caused by direct S-sulfhydration of HCN proteins and/or to modifications of intracellular cAMP/cGMP levels resulting from phosphodiesterase inhibition by H2S. These findings may open novel perspectives to modulate If function and dysfunction in cardiac pacemaker cells and working myocytes.